A Novel Approach for Conservative Management of Placenta Accreta Spectrum Disorder Cases: Experience of a Single Surgeon - Ahmet Yalınkaya; Süleyman Cemil Oğlak (Journal of Pregnancy)
Conclusions: We recommend this procedure as a novel technique and a robust and safe alternative to peripartum hysterectomy and other conservative surgical management procedures for cases with complete PP accompanied with PAS. This technique preserves the uterus as well as reduces blood loss, and transfusion requirement, and thus maternal morbidity and mortality in PAS cases.